Wnt/Beta-catenin/Esrrb signalling controls the tissue-scale reorganization and maintenance of the pluripotent lineage during murine embryonic diapause - Rui Fan (Nature Portfolio, 2020)
Embryonic diapause is a state of dormancy with poorly understood mechanisms of embryo intrinsic regulation. Here, the authors show that murine diapause is a dynamic process, where tissue-scale reorganization of the pluripotent lineage is controlled in an autocrine manner by the Wnt/b-catenin/Esrrb signalling cascade.